2012
DOI: 10.1108/09596111211197782
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and branding behavior in Taiwanese hotels

Abstract: PurposeThe purpose of this paper is to investigate the messages delivered by transformational leaders to front‐line employees to build an organizational brand climate and encourage employees' branding behaviors, to attain better company performance within the Taiwanese hotel industry.Design/methodology/approachSurvey data were obtained from 34 human resource managers and 326 customer contact employees working in Taiwanese hotels.FindingsTransformational leadership was found to have both direct and indirect pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…For example, based on Asree et al (2010), leadership competency influences hotel performance. Also, Uen et al (2012) found that transformational leadership leads to a better company performance within the hotel industry. The main contribution of this research is to suggest empirical evidence to support the impact of spiritual leadership on hotel performance.…”
Section: Managerial Implicationsmentioning
confidence: 98%
“…For example, based on Asree et al (2010), leadership competency influences hotel performance. Also, Uen et al (2012) found that transformational leadership leads to a better company performance within the hotel industry. The main contribution of this research is to suggest empirical evidence to support the impact of spiritual leadership on hotel performance.…”
Section: Managerial Implicationsmentioning
confidence: 98%
“…Recent research in hospitality (Uen et al, 2012) and in tourism on micro DMOs (Zach, 2016) has highlighted the role of 'transformational leadership' in innovative behaviour. This induces employees' trust and commitment, and creates an organisational brand climate where members have shared perceptions (Liao and Chuang, 2007).…”
Section: Organisational Innovativeness Collaborative Innovation and mentioning
confidence: 99%
“…The business environment comprises several unfavorable factors such as layoffs, downsizing, and loss of job security, and other related forms of organizational change have eroded the psychological contract between employees and employers (Epitropaki, 2013;Ye et al, 2012). In addition, supervisor's influence to support superior service is critical to tourism organizations (Asree et al, 2010;Gill et al, 2010;Testa and Sipe, 2012;Uen et al, 2012). Therefore, when employees cannot perceive the fulfillment of commitments by organizations or employers, such as in terms of pay, promotion, and job security, employees exhibit decreased willingness to devote their skill, effort, knowledge, and loyalty (Cavanaugh and Noe, 1999), which leads to an increase in the turnover intention (Collins, 2010;Sutton and Griffin, 2004).…”
Section: Introductionmentioning
confidence: 98%